High school English-as-a-foreign-language teachers’ emotional labor and job satisfaction: A latent profile analytical approach - Zhu, Shenhai; Zhou, Maojie (Frontiers in Psychology, 2022)
Previous studies have primarily used variable-centered approaches to explore correlations between English-as-a-foreign-language (EFL) teachers’ emotional labor and outcome variables. A fundamental but unresolved question is whether teachers employ multiple emotional labor strategies in the workplace. This study used the latent profile analysis (LPA) to explore the profiles of EFL teachers’ emotional labor and the relationship between the profiles and job satisfaction based on a questionnaire survey of 365 high school EFL teachers in China. The results indicated the existence of three emotional labor profiles—agreeable, neutral and emotional—that were characterized by different combinations of surface acting (SA), deep acting (DA), and expression of naturally felt emotion (ENFE). The profiles of EFL teachers who predominantly relied on ENFE and DA had the most adaptive patterns of job satisfaction, whereas the profiles of teachers who reported higher levels of SA, regardless the level of ENFE and DA, experienced lower levels of job satisfaction. These findings provide a person-centered methodological data support for exploring the relationship between emotional labor and EFL teachers’ job satisfaction.